2010
DOI: 10.18832/kp2010019
|View full text |Cite
|
Sign up to set email alerts
|

Seed mycoflora of malting varieties and lines of spring barley in localities Kroměříž and Žabčice.

Abstract:  1 ÚVODKvalita sladovnického ječmene je výrazně ovlivňována agroenvironmentálními faktory, které působí i na složení populace mikroflóry zrn a intenzitu napadení. Zrna bez populací mikroorganismů se objevují zcela výjimečně. Mezi významné patogeny zrna ječmene, a současně i producenty mykotoxinů, patří např. druhy rodu Fusarium, Alternaria, Aspergillus, Penicillium aj., z nichž některé druhy jsou schopny v průběhu sladování zvyšovat svoji četnost i aktivitu. Zvýšená pozornost je věnována především druhům r. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…during the 2018 and 2019 harvests are in line with previous studies [55][56][57]. Our findings about the mycoflora spectrum of malting barley and the corresponding malt in Germany are similar to those reported by other authors regarding barley cultivars in the Czech Republic [58], Slovak Republic [57], Romania [32], Lithuania [18] and Africa [59] (with the application of traditional microbiological methods).…”
Section: Mycological Status-agar Plate Methodssupporting
confidence: 92%
“…during the 2018 and 2019 harvests are in line with previous studies [55][56][57]. Our findings about the mycoflora spectrum of malting barley and the corresponding malt in Germany are similar to those reported by other authors regarding barley cultivars in the Czech Republic [58], Slovak Republic [57], Romania [32], Lithuania [18] and Africa [59] (with the application of traditional microbiological methods).…”
Section: Mycological Status-agar Plate Methodssupporting
confidence: 92%
“…Ingle, 1990 [68], studied the transmission and control of pearl millet seed-borne fungi and reported that seed samples collected from a farmer's field were more discoursed which was attributed to frequent rains during the seed development stages, high seed moisture content and a prolonged storage period deteriorating the seed quality. The quality of the seeds at the time of sowing depends on the quality of the seeds that entered storage and how well they were stored [69][70][71]. Seeds quality does not improve in storage, so inferior seeds in the store will finally end up as inferior seeds at sowing, no matter how much care is taken during storage [38,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the fungicide may act as a stress factor for F. culmorum or F. graminearum, resulting in higher toxin production [57]. It should be noted that both F. culmorum and F. graminearum have been detected in fungicide-treated harvested barley [58]. HT-2 levels were reduced by solubilisation in the steeping water during the malting process.…”
Section: Mycotoxinsmentioning
confidence: 98%